PENGARUH PROFITABILITAS, KUALITAS AUDIT, NILAI PERUSAHAAN, DEWAN KOMISARIS INDEPENDEN DAN UKURAN DEWAN KOMISARIS TERHADAP MANAJEMEN LABA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Syahrani, Tiara (JURNAL FAIRNESS, 2019)
This study aimed to empirically examine the effect of profitability, audit quality, value company, independent board of commissioner, size of board of commissioner to earning management. The population of the data is the entire manufacturing companies listed on the Indonesia Stock Exchange in the period 2014 to 2017.This study used the purposive sampling method to select sample from the population. Based on this method, sample of 55 manufacturing firms were obtained from the period 2014-2017. The multiple linear regression was used to analysis data. Proxy measurements for earning management is using modified Jones models.The result of multiple regression analysis show that the profitability and size of board of commissioner positivly affecting to earning management, audit quality and independent board of commissioner negatively affecting earning management. While the value company has not effect to earning management.